National context drives concerns. (October 2018) - Sovacool, Benjamin
The concept of energy security is multifaceted, and can cover a number of seemingly distinct energy- and climate-related risks. Now, research shows that public opinion about energy security reflects the geographic variation in these risks, such that cross-country differences in public concern are explained by national energy context and indicators.